(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper provides a comprehensive analysis of environmental law in India, examining its evolution, scope, and the challenges it faces in the contemporary context. The study explores the rising complexity of environmental crimes, driven by technological advances and changing societal dynamics, and assesses the effectiveness of existing legal frameworks at both national and international levels. Key Indian statutes and constitutional provisions are reviewed alongside major global conventions and protocols, highlighting the interconnectedness of domestic and international enviro-legal regimes. The paper argues that while India possesses a robust legislative arsenal, enforcement gaps and the rapid emergence of new environmental threats necessitate ongoing legal reform and greater public awareness. The conclusion offers targeted suggestions for strengthening environmental governance in India, including alignment with international norms, grassroots education, and enhanced legal enforcement.